Internalisasi Nilai-nilai Religius melalui Kegiatan Ekstrakurikuler Kerohanian Islam di SMP Negeri 47 Surabaya - Warsito Hadi (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2020)
This study aims to analyze the implementation of the internalization of religious values ​​through extracurricular activities of Islamic spirituality at SMPN 47 Surabaya. This research is a descriptive qualitative case study type. The results showed that the process of internalizing religious values ​​through extracurricular activities of Islamic spirituality includes the values ​​of faith, sharia, and morals using exemplary methods, habituation, supervision, advice and punishment. The activities include: giving examples of Muslim dress, getting students used to praying in the Duha and Asr congregations, getting students to perform Friday prayers, pondok romadhon, zakat fitrah / maal, commemoration of the Prophet Muhammad SAW's birthday, and istighosah. The internalization process goes through three stages, namely value transformation, value transaction, and value transinternalization. The internalization process is supported by harmonious cooperation with fellow teachers, most students come from religious families and the availability of infrastructure needed by students. To be more effective, the authors recommend several things: First, there must be synergy between teachers and parents so that efforts to internalize Islamic religious values ​​are sustainable in the family environment. Second, there needs to be periodic evaluation, so that the advantages and disadvantages can be identified precisely.